2015
DOI: 10.3174/ajnr.a4473
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 2-Phase Parathyroid CT for the Preoperative Localization of Parathyroid Adenomas in Primary Hyperparathyroidism

Abstract: BACKGROUND AND PURPOSE:Minimally invasive parathyroidectomy requires accurate preoperative localization of suspected adenomas, and multiphase CT allows adenoma characterization while providing detailed anatomic information. The purpose of this study was to assess the feasibility of a protocol using only arterial and venous phases to localize pathologic glands in patients with primary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…However, accuracy of parathyroid imaging reported in the literature varies between 56%‐84% for US and 59%‐93.7% for MIBI . Currently, there is no evidence that additional imaging with CT, MRI or new nuclear scans would result in better localisation . Therefore, single modality imaging has been considered not accurate enough to guide successful MIP and this has led to the concept of “concordant imaging results”, when two or more scans, usually US and MIBI but sometimes CT or MRI, can agree on site and number of abnormal glands.…”
Section: Discussionmentioning
confidence: 99%
“…However, accuracy of parathyroid imaging reported in the literature varies between 56%‐84% for US and 59%‐93.7% for MIBI . Currently, there is no evidence that additional imaging with CT, MRI or new nuclear scans would result in better localisation . Therefore, single modality imaging has been considered not accurate enough to guide successful MIP and this has led to the concept of “concordant imaging results”, when two or more scans, usually US and MIBI but sometimes CT or MRI, can agree on site and number of abnormal glands.…”
Section: Discussionmentioning
confidence: 99%
“…Performance of 4DCT in most previous studies is based on subjective assessment of lesion enhancement and washout patterns in different phases . Based on the observation that parathyroid adenomas enhance maximally in arterial phase, some studies have suggested dual‐phase CT, to reduce the radiation dose . On the contrary, Bahl et al .…”
Section: Discussionmentioning
confidence: 99%
“…introduced four‐dimensional computed tomography (4DCT) as a localization modality and reported its higher sensitivity (70%) for quadrant‐specific parathyroid lesion localization as compared to that of ultrasonography (USG) (29%) and sestamibi SPECT/CT (33%). Since then, several groups have reported its performance with some modifications in varied cohorts of PHPT patients . However, radiation exposure to neck by 4DCT is relatively high and limits its use as a first‐line investigation modality.…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, a new approach using the radiopharmaceutical 99m Tc-MIBI was reported for identification and localization of PTG and this imaging method gradually replaced the previous subtraction method based on 201 Tl/ 99 Tc 22 .Several investigators confirmed the use of this technique for the identification of abnormal PTG using either MIBI alone or with subtraction imaging. The sensitivity was in range of 71-93% [23][24][25] . Numerous studies comparing scintigraphy and ultrasonography suggest that both methods have similar sensitivities and specificities in the detection of solitary adenomas with a range of 68%-95% for scintigraphy and a range of 72%-89% for ultrasonography [25][26][27] .…”
Section: Introductionmentioning
confidence: 96%